Water consumption patterns of 110 cities in the Yangtze River Economic Belt in 2015 - Sun, Boyang; Li, Fapeng (Frontiers in Earth Science, 2022)
How to formulate scientific and effective water-saving policies is of great significance for the sustainable use of water resources. As a country with the largest water consumption in the world, China has been committed to formulating scientific and effective water-saving policies. However, due to geospatial variations of water consumption in different regions, how to formulate efficient water-saving policies which suit for different local characteristics has always been a key issue to be solved. In a quest to understand the water consumption patterns, this study first adopted a dual evaluation index system combining Gini coefficient and Global Moran’s Index to classify different types of water consumption. Taking 110 cities in the Yangtze River Economic Belt as research objects, the water consumption of 110 cities was divided into 9 types. According to each type, a targeted water-saving policy is given. This study provides important theoretical support for the efficient management of water resources in the Yangtze River Economic Belt, and provides reference for water resources management in other regions at the same time.